Medicinal plants and university extension: experience report in COVID-19 times (Research, Society and Development, 2020)
This article is relevant to report the experience of students of the Dentistry course in a university extension project, developed with public school teachers in conjunction with the City Hall and the Parish of Nossa Senhora da Conceição in Araruna-PB. The project aims to train students about phytotherapy and its relationship with dentistry, rescuing the use of medicinal plants and enabling future dentists to prescribe plant drugs. It is a descriptive study, an experience report, lived by students of the Dentistry course at the State University of Paraíba (UEPB). The project's methodology consists of training students through short courses, lectures, round tables and practice in the local community. However, given the context of the new Coronavirus pandemic, it became necessary to adapt activities remotely through digital tools such as the Google Meet® platform and the project's social networks. As a result, there was the participation of extension workers in online scientific events, as well as the creation and dissemination of informative content based on scientific articles, thus spreading greater knowledge about the importance of medicinal plants for health. Therefore, it was seen that, even though there were changes regarding the execution of the project, the activities were carried out successfully, resulting in the students' knowledge of scientific knowledge and a closer relationship with the community with the theme addressed, proving the effectiveness of the project. university extension in a pandemic period.